Quel est le profil de l’enseignant d’histoire idéal selon les élèves sur le point de se soumettre à l’épreuve unique ministérielle d’histoire ? - Pageau, Laurie (Canadian Journal of Education/Revue canadienne de l’éducation, 2026)
Several studies have documented the presence of very different epistemological understandings of history in Quebec schools. For this article, we document one facet of secondary school students’ representations of history: a thematic analysis of the 305 respondents’ answers enables us to see what expectations adolescents have of their history teachers, and also to highlight the different expectations of their teachers of students with a more transmissive vision of history, as opposed to those who have developed a more constructivist vision of learning history .